Effect of helical force on the stationary convection in a rotating ferrofluid - MONWANOU, VINCENT ADJIMON; CHABI OROU, JEAN BIO (My University, 2020)
In this paper we studied the onset of instability in a horizontal layer of a rotating ferrofluid in the presence of the helical force. The analytical expression of the Rayleigh number of the system is determined as a function of the dimensionless numbers obtained. Then, the effect of each di- mensionless parameter is studied. The helical force, the binary parameter ψ then the magnetic parameters M 1 , M 3 and ψ m accelerate the onset of stationary convection whereas the rotation and the magnetic parameter M 2 delay it. Also all the magnetic parameters, the binary parameter and the rotation cause the convection rolls to shrink while only the helical force increases the size of these structures.
Keywords: Thermal convection; Magnetic fluid; Helical force; Rotation